Single-cell RNA-seq reveals ectopic and aberrant lung-resident cell populations in idiopathic pulmonary fibrosis - Adams, Taylor S.; Schupp, Jonas C.; Poli, Sergio; Ayaub, Ehab A.; Neumark, Nir; Ahangari, Farida; Chu, Sarah G.; Raby, Benjamin A.; DeIuliis, Giuseppe; Januszyk, Michael; Duan, Qiaonan; Arnett, Heather A.; et al. (Science advances, 2020)
Human lung single-cell atlas reveals the complexity and diversity of aberrant cellular populations in pulmonary fibrosis. We provide a single-cell atlas of idiopathic pulmonary fibrosis (IPF), a fatal interstitial lung disease, by profiling 312,928 cells from 32 IPF, 28 smoker and nonsmoker controls, and 18 chronic obstructive pulmonary disease (COPD) lungs. Among epithelial cells enriched in IPF, we identify a previously unidentified population of aberrant basaloid cells that coexpress basal epithelial, mesenchymal, senescence, and developmental markers and are located at the edge of myofibroblast foci in the IPF lung. Among vascular endothelial cells, we identify an ectopically expanded cell population transcriptomically identical to bronchial restricted vascular endothelial cells in IPF. We confirm the presence of both populations by immunohistochemistry and independent datasets. Among stromal cells, we identify IPF myofibroblasts and invasive fibroblasts with partially overlapping cells in control and COPD lungs. Last, we confirm previous findings of profibrotic macrophage populations in the IPF lung. Our comprehensive catalog reveals the complexity and diversity of aberrant cellular populations in IPF.